SOCIAL NORMS AS A MODERATION VARIABLE IN THE RELATIONSHIP OF TAXPAYER AWARENESS TO THE COMPLIANCE OF PBB-P2 TAXPAYERS IN AMBON CITY GOVERNMENT - SEMY PESIRERON; JULIANA KESAULYA (INTERNATIONAL JOURNAL OF MULTI SCIENCE, 2020)
This research aims to empirically test the influence of independent variables, namely; taxpayer awareness of taxpayer compliance, as well as to empirically analyze the influence of varied social norms in moderating the relationship of taxpayer awareness to taxpayer compliance in paying Earth and Rural and Urban Buildings Tax (PBB-P2) in Ambon City. This research is empirical research with sampling techniques used is purposive sampling and data collection using survey methods. The analysis used was multiple linear regression with hypothetical tests using t-statistics to test partial regression coefficients as well as F-statistics to test influence together with a confidence level of 0.005 or 5%.The results of this study showed there was an insignificant influence of taxpayer awareness on taxpayer compliance in paying taxes. There is a significant influence of variable moderation of social norms on the relationship between taxpayer awareness and taxpayer compliance.